Rectification of impaired adipose tissue methylation status and lipolytic response contributes to hepatoprotective effect of betaine in a mouse model of alcoholic liver disease. (2nd July 2014) - Dou, Xiaobing; Xia, Yongliang; Chen, Jing; Qian, Ying; Li, Songtao; Zhang, Ximei; Song, Zhenyuan
<x xml:space="preserve">Abstract</x> Background and Purpose Overactive lipolysis in adipose tissue contributes to the pathogenesis of alcoholic liver disease (ALD); however, the mechanisms involved have not been elucidated. We previously reported that chronic alcohol consumption produces a hypomethylation state in adipose tissue. In this study we investigated the role of hypomethylation in adipose tissue in alcohol‐induced lipolysis and whether its correction contributes to the well‐established hepatoprotective effect of betaine in ALD. Experimental Approach Male C57BL/6 mice were divided into four groups and started on one of four treatments for 5 weeks: isocaloric pair‐fed (PF), alcohol‐fed (AF), PF supplemented with betaine (BT/AF) and AF supplemented with betaine (BT/AF). Betaine, 0.5% (w v−1), was added to the liquid diet. Both primary adipocytes and mature 3T3‐L1 adipocytes were exposed to demethylation reagents and their lipolytic responses determined. Key Results Betaine alleviated alcohol‐induced pathological changes in the liver and rectified the impaired methylation status in adipose tissue, concomitant with attenuating lipolysis. In adipocytes, inducing hypomethylation activated lipolysis through a mechanism involving suppression of protein phosphatase 2A (PP2A), due to hypomethylation of its catalytic subunit, leading to increased activation of hormone‐sensitive lipase (HSL). In line with in vitro observations, reduced PP2A catalytic subunit methylation and activity, and enhanced HSL activation, were observed in adipose tissue of alcohol‐fed mice. Betaine attenuated this alcohol‐induced PP2A suppression and HSL activation. Conclusions and Implications In adipose tissue, a hypomethylation state contributes to its alcohol‐induced dysfunction and an improvement in its function may contribute to the hepatoprotective effects of betaine in ALD.